Reimagining Our Futures Together : A New Social Contract for Education (Educational Research E-Books Online, Collection 2026., 2025)
In Reimagining Our Futures Together: A New Social Contract for Education , the International Commission on the Futures of Education presents a compelling vision for transforming education to address global challenges. Drawing from a global consultation engaging approximately one million people, the report advocates for a new social contract grounded in human rights, social justice, and sustainability. It emphasizes the need for education systems that promote cooperation, solidarity, and ecological responsibility. By highlighting innovative practices and diverse perspectives, the report offers actionable recommendations to build peaceful, just, and sustainable futures through education.